The Luminaries - Catton, Eleanor (London : Granta, 2013)
It is 1866, and Walter Moody has come to make his fortune upon the New Zealand goldfields. On the night of his arrival, he stumbles across a tense gathering of twelve local men, who have met in secret to discuss a series of unsolved crimes. A wealthy man has vanished, a whore has tried to end her life, and an enormous fortune has been discovered in the home of a luckless drunk. Moody is soon drawn into the mystery: a network of fates and fortunes that is as complex and exquisitely patterned as the night sky. The Luminaries is an extraordinary piece of fiction, which more than fulfils the promise of The Rehearsal. Like that novel, it is full of narrative, linguistic and psychological pleasures, and has a fiendishly clever and original structuring device. Written in pitch-perfect historical register, richly evoking a mid-19th century world of shipping and banking and goldrush boom and bust, it is also a ghost story, and a gripping mystery.
Keywords: Crime; Prostitutes; Trials (Murder)